Cardiorespiratory Fitness among Adolescent Girls - Bhavani, A. (Research Journal of Physical Education Sciences, 2016)
Cardio respiratory fitness is an integrated function of circulatory and working muscles and organs for prolong activity. Purpose of the study was to examine the cardio respiratory fitness different age groups such as 14, 15 and 16 years of school girls. Cardio respirato assess the endurance ability of girls. To assess the cardio respiratory fitness ability the subjects have been selected from Jaffna Zone in Sri Lanka. 1000 subjects have been recruited from a age group totally 3 age group for this study. 9 minutes Run/ Walk test was conducted to assess the ability of cardio respiratory fitness. During minutes covered distance was recorded in meter for data interpretation. Analysis of variance find out significant different. The result revealed that significant differences were observed among three group. The 16 year girls was higher in cardio respiratory fitness compared to 15 and 14 years, 15 years also was better concluded that when age increase the cardio respiratory fitness also increase during adolescence.
Keywords: Cardiorespiratory; Adolescence